A fast code for channel limb radiances with gas absorption and scattering in a spherical atmosphere. (May 2017) - Eluszkiewicz, Janusz; Uymin, Gennady; Flittner, David; Cady-Pereira, Karen; Mlawer, Eli; Henderson, John; Moncet, Jean-Luc; Nehrkorn, Thomas; Wolff, Michael
Abstract: We present a radiative transfer code capable of accurately and rapidly computing channel limb radiances in the presence of gaseous absorption and scattering in a spherical atmosphere. The code has been prototyped for the Mars Climate Sounder measuring limb radiances in the thermal part of the spectrum (200–900 cm −1 ) where absorption by carbon dioxide and water vapor and absorption and scattering by dust and water ice particles are important. The code relies on three main components: 1) The Gauss Seidel Spherical Radiative Transfer Model (GSSRTM) for scattering, 2) The Planetary Line-By-Line Radiative Transfer Model (P-LBLRTM) for gas opacity, and 3) The Optimal Spectral Sampling (OSS) for selecting a limited number of spectral points to simulate channel radiances and thus achieving a substantial increase in speed. The accuracy of the code has been evaluated against brute-force line-by-line calculations performed on the NASA Pleiades supercomputer, with satisfactory results. Additional improvements in both accuracy and speed are attainable through incremental changes to the basic approach presented in this paper, which would further support the use of this code for real-time retrievals and data assimilation. Both newly developed codes, GSSRTM/OSS for MCS and P-LBLRTM, are available for additional testing and user feedback. Highlights: An accurate and fast radiation code for spherical atmospheres is presented Code considers gaseous absorption and scattering to compute channel limb radiances Uses Gauss Seidel Spherical Radiative Transfer Model, Optimal Spectral Sampling A version of the well-known LBLRTM radiation code suitable for Mars is presented